Considering the combinatorial effects of on-site distributed generation and battery-to-X option availability in electric vehicle battery swap station operation - Erdinc, Ozan (ELSEVIER, 2021)
Amongst different options to supply the energy demand of electric vehicles, battery swap based operational concept may be a promising solution for wider integration of electric vehicles. However, wider adoption of battery swap solution heavily relies on implementation of effective business models and new operational concepts. In this study, the combinatorial effects of photovoltaic system based distributed generation unit as well as battery-to-X availability in an EV battery swap station operation are analysed via a Mixed-Integer Linear Programming framework based energy management system model. The aim of this study is to ensure a highly flexible energy management system model for such a structure composed of Battery-to-Battery, Grid-to-Battery, Battery-to-Grid, Photovoltaic-to-Battery, Photovoltaic-to-Grid transactions options. Besides, the Quality-of-Service level and State-of-Health condition variation of the battery stock in the swap station are also considered as constraints of the overall system model. The results reveal the benefits of constructing such a highly flexible operation model with the mentioned quality and operational sustainability oriented constraints. (c) 2021 Elsevier Ltd. All rights reserved.
Keywords: B2X operational flexibility; Battery state-of-health; Battery swap station; Distributed generation; Energy management; STRATEGY; SYSTEMS; DEMAND; Energy & Fuels; Engineering